Developing Tutorial Video for Enhancing Elementary School Students’ Process Skills in Science - Mahlianurrahman Mahlianurrahman; Fetro Dola Syamsu (Jurusan PGMI FTIK IAIN Metro Lampung, 2019)
The purpose of this research was to prove the improvement and effectiveness of video tutorial media as a result of development. The model in this study applied the research and development model of Borg & Gall. The procedure of this study included 9 steps, namely a) preliminary research and collecting initial information; b) planning; c) developing product drafts; d) conducting an initial trial; e) revising the results of limited trials; f) conducting field trials; g) making product improvements resulting from field trials; h) conducting operational field trials; and i) making improvements to the final product. Product testing was carried out on the fifth grade elementary school students in South Aceh. Data collection techniques used observation. The observation sheet was used to measure students’ process skills. The feasibility of the media was analyzed by score conversion using a scale of 5. Media effectiveness was analyzed by gain score, and t-test. The results of this study were video tutorial media products on style material that are feasible to apply to science learning on student process skills.